DEFINING QUALITY CRITERIA IN SITUATIONAL METHOD ENGINEERING - Azzouz, Samir; Kraiem, Naoufel; Ghezala, Henda Ben (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Method engineering is a field of engineering that has been created a need expressed by engineers. These engineers faced problems in using conventional methods such as SSADM, DSDM, OOAD...In this way, Method engineering was created to intend to develop methods to meet these needs. Therefore, these methods have been employed in a wide range of projects led by these architects. In other contexts, we are led to customize a method for a particular project. The method obtained is called Situational Method (SM).In this paper, we define the basics in order to achieve the monitoring of Situational Method quality in the early stages of its setting up to its effective exploitation.Â In addition, we identify criteria that allow us to evaluate the construction of a method in terms of quality.Finally, we discuss the choices we have made in this paper and challenges that we have to raise to achieve this quality concept.